Influence of Masticatory Behavior on Muscle Compensations During the Oral Phase of Swallowing of Smokers - Silva, Gabriela Rodrigues da; Rech, Rafaela Soares; Vidor, Deisi Cristina Gollo Marques; Santos, Karoline Weber dos (International Archives of Otorhinolaryngology, 2019)
Introduction Chewing and swallowing are physiologically interconnected functions, which share motor structures and supranuclear regions of the central nervous system (CNS), involving a sensorimotor synchrony.Objective To analyze the influence of masticatory behavior on muscular compensations in the oral phase of swallowing in smokers compared with nonsmokers.Methods A cross-sectional study comparing smokers and nonsmokers composed of 24 participants in each group. The aspects of food crunching, masticatory pattern, masticatory speed, atypical muscular contractions, and lip closure were analyzed during mastication. In swallowing, aspects of contraction of the orbicular and mental muscles, head movement and presence of deglutition, mastication, smoking, and of stomatognathic system of residues after swallowing were characterized.Results Statistically significant differences were identified between the study groups related to food grinding pattern, masticatory velocity, and mental contraction during swallowing. There was no significant association between masticatory function and compensations during swallowing.Conclusion Differences were observed in the pattern of chewing and swallowing in smokers compared with nonsmokers, but no influence of masticatory performance was observed in the presence of muscle compensations during the oral phase of swallowing.
Keywords: deglutition; mastication; smoking; stomatognathic system